Public Chaos: Alleged Fatwa on Boycotting and the Fear of Missing Out on Israeli Products in Indonesia - Husna, Nurul; Irfan, Andi Farahdhiba; Juliandi, Budi; Herlambang, Saifuddin; Fadhlunasyifa, Fadhlunasyifa (Universitas Islam Negeri Jakarta, 2025)
The following text presents a synopsis of the abstract. As the conflict between Israel and Palestine intensifies, the Indonesian Ulama Council (MUI) has issued a fatwa that has generated controversy in various mass media, particularly on social media platforms. The objective of this study is to examine whether the